(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Autism spectrum disorder (ASD) is a range of complex neurodevelopment disorders, characterized by social impairments, communication difficulties, and restricted, repetitive, and stereotyped patterns of behavior. There are various degrees of fine motor skills deficits like inability to eat, inability to use a computer, difficulties in personal care tasks such as dressing and grooming, difficulties in holding pen or pencil in hand,difficulties in drawing line on paper, difficulties in turning pages, handwriting deficits, and difficulties in the writing processfound along with problems in manual dexterity among children with Autism. Lacking of fine motor skills adversely affects writing, drawing as well as many functional activities involving the hands and arms directly affects academic activities. Motor skills especially fine motor skills among children with autism can be developed through innovative practices like- Neuro Developmental Therapy (NDT), Sensory Integration Therapy (SIT), .This paper highlights about the role of Neurodevelopmental therapy in improving fine motor skills among children with Autism. Various Approaches which are effective methods used as physiotherapy interventions and management to improve fine motor skills in children with Autism.